Totalitarianism: Between Religion and Science - Todorov, Tzvetan (Totalitarian movements and political religions, 2001)
This article concentrated upon one of the key components of modern totalitarian regimes, mainly 'scientism', that is the belief that a totally fragmented world can be transformed by the allegedly absolute knowledge of biology, economics, 'social science', and so forth. These beliefs derive from the popular need for transcendence and the search for utopia which explains the mass attraction of the carious totalitarian projects. While democracies should have no part in trying to incarnate utopia through violence, they need to be aware of the non-material longings which totalitarians claimed to satisfy.